Effect of Interaction of Salt and Different Concentrations of Seaweed Extract on Balady Lime Seedlings - Alijuburi, Hameed Jasim; Al-Masry, Hasan (Annals of Arid Zone, 2025)
The results revealed that Balady lime seedlings (Cimrs aurantifolia) ould be irrigated with waters having nioderate concentration of salt (0.2%) for 213- days without reduction in relative growth rate (RGR). Seaweed extract did not antagonize the salt effect on relative growth rate of Balady lime seedlings. Foliar application of 1% seaweed extract niarginally increased the RGR. Other concentrations of salt, or seaweed extract alone, or in combination. reduced the RGR. Application of 0.6% salt significantly increased the root dry matter over the control, but seaweed extract with salt or alone had no significant effect on root dry matter. Application of 0.6% salt solution for 250 days resulted in a significant increase in sten1 dty matter over the control, but did not respond significantly to foliar application of different concentrations of seaweed extract.Leaf dry niatter of Balady linie seedling was significantly higher when irrigated with 0.2% salt for 250 days whereas. application of different concentrations of salt or seaweed extract for 250 days had no significant effect on stem diameter.